THERMOSTRESSED STATE OF CYLINDER SLUG, HEATED IN RADIATION-CONVECTION CONTRAFLOW - V. I. Timoshpolski; Ju. S. Postolnik; P. E. Ratnikov (Литьë и металлургия, 2005)
The solving of the problem of thermoelasticity at heating of cylindric slugs in terms of radiation-convection contraflow is presented.